FINANCIAL PSYCHOLOGY, FINANCIAL LITERACY, AND FINANCIAL BEHAVIOR: THE MODERATING ROLE OF MAQASHID SHARIAH AMONG CIVIL SERVANTS IN TERNATE CITY - Ridwan, Muhammad; Basri, Anjani (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2026)
This study examines how financial psychology and financial literacy influence consumptive and investment behavior among civil servants, with Maqashid Shariah serving as a moderating variable. Despite extensive research on financial behavior, limited empirical evidence explains how shariah-based ethical values condition the effects of psychological and rational financial factors, particularly in the public sector. Using a quantitative approach, data were collected through Likert-scale questionnaires from 196 civil servants in Ternate City and analyzed using regression and moderation analysis. The findings indicate that financial psychology positively affects consumptive behavior, while financial literacy has a negative effect. Maqashid Shariah negatively moderates the relationship between financial psychology and consumptive behavior and positively moderates the relationship between financial literacy and consumptive behavior. Regarding investment behavior, financial psychology shows no significant effect, whereas financial literacy exerts a positive influence. Furthermore, Maqashid Shariah positively moderates the relationship between financial literacy and investment behavior. Theoretically, these findings extend Islamic behavioral finance by integrating ethical moderation into conventional financial behavior models. Practically, the results suggest that value-based financial education for civil servants can reduce excessive consumption and promote ethical investment decisions.